Elemental depth imaging of solutions for monitoring corrosion process of steel sheet by confocal micro X‐ray fluorescence. (29th May 2014) - Hirano, S.; Akioka, K.; Doi, T.; Arai, M.; Tsuji, K.
<x xml:space="preserve">Abstract</x> Non‐destructive and non‐contact analysis has been in demand on numerous occasions. Confocal micro X‐ray fluorescence analysis enables depth‐selective elemental analysis of solid samples in the laboratory. In this paper, we applied this technique for imaging elemental distributions in solutions. A low‐carbon steel sheet was placed in artificial seawater (NaCl: 3.5 mass%), and the corrosion process in the solution was observed. A depth image of Fe Kα intensity in the NaCl solution was obtained by using this technique. The Fe Kα intensity in the solution was measured with corrosion time by sequential line analysis at a fixed lateral position. The corrosion of Fe from the steel sheet, the migration of Fe ions in solution, and their condensation near a polymer window were successfully monitored. Copyright © 2014 John Wiley & Sons, Ltd.